2019
DOI: 10.29026/oea.2019.190011
|View full text |Cite
|
Sign up to set email alerts
|

A review on control methodologies of disturbance rejections in optical telescope

Abstract: Structural vibrations in Tip-Tilt modes usually affect the closed-loop performance of astronomically optical telescopes. In this paper, the state of art control methods-proportional integral (PI) control, linear quadratic Gaussian (LQG) control, disturbance feed forward (DFF) control, and disturbance observer control (DOBC) of Tip-Tilt mirror to reject vibrations are first reviewed, and then compared systematically and comprehensively. Some mathematical transformations allow PI, LQG, DFF, and DOBC to be descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…It has been taken in a lot of fields into use, such as target tracking, laser communication, adaptive optics [1]- [4]. The main task of the optoelectronic tracking system is line-of-sight (LOS) tracking, and line-of-sight tracking uses the image sensor to capture dynamic target information to close the loop in real-time [5]. To attain better disturbance overcome and tracking performance of the optoelectronic tracking system, people have proposed a great diversity of LOS tracking methods, such as PID [6], speed delay compensation [7], and disturbance observer based on multi-loop feedback control [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been taken in a lot of fields into use, such as target tracking, laser communication, adaptive optics [1]- [4]. The main task of the optoelectronic tracking system is line-of-sight (LOS) tracking, and line-of-sight tracking uses the image sensor to capture dynamic target information to close the loop in real-time [5]. To attain better disturbance overcome and tracking performance of the optoelectronic tracking system, people have proposed a great diversity of LOS tracking methods, such as PID [6], speed delay compensation [7], and disturbance observer based on multi-loop feedback control [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tip-tilt vibrations induced by platform moving, equipment vibration, wind shaking which exhibited complexity in terms of frequency and amplification, and beam jitter in optical link affect the imaging quality and even damage the closed-loop stability [4]- [6]. Furthermore, the long exposure time required for a better signal-to-noise ratio (SNR) images brings amounts of time delay [7], [8], which extremely restricts the closed-loop bandwidth, which makes the highfrequency disturbance suppression beyond control bandwidth become a technical barrier [9], [10]. Developing new control algorithms to suppress disturbance, especially high-frequency disturbance, is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these control methods achieve good results in low-frequency disturbance suppression. Nevertheless, the inaccurate identification of the system model and the disturbance model could reduce the effectiveness of disturbance suppressions and even damage the system stability in the high-frequency domain [10]. The repetitive digital controller, which can update the control parameters quickly in real-time, is widely used in various high-precision systems, including hard disk drivers, periodic trajectories, and harmonics compensation of power inverters [22]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…Zaher M. Kassas derived the optimal control rate of the control system of Extremely large telescopes ELT, and found that H 2 and H ∞ had the best imaging performance in the case of wind disturbance (Zaher & Rober 2012). Tao Tang analyzed and compared the suppression effects of PI, LQG, DFF (disturbance feedforward control) and DOBC (disturbance observer control) on disturbance of different frequencies (Tang et al 2019). Among them, DOBC has a great suppression ability on disturbance.…”
Section: Introductionmentioning
confidence: 99%